Determinants of Environmental, Social and Governance (ESG) Ratings in Nigerian Listed Banks - Ogboro, Efafosa; Omokhudu, Okun; Odia, James O (Accounting Department,, 2024)
Purpose - The study empirically investigates the determinants of ESG ratings in Nigerian banks, contributing to the limited literature on ESG determinants in emerging markets. Findings indicate significant relationships between institutional ownership, firm age, and ESG ratings, with practical implications for regulatory frameworks and corporate governance policies in Nigeria’s banking sector. Design/methodology/approach - A longitudinal research design is used for empirical analysis in the study. The population used in the study is the Nigerian Exchange Group (NGX) listed banks as of the year-end, 31st December 2022. A census of seventeen (17) banks was studied over a period of seven (7) years (2016-2022). Descriptive statistics, correlation analysis, and panel regression analysis with a fixed effect model were used for quantitative data analysis. Findings – Empirical results reveal that institutional ownership and firm age positively and significantly impact the ESG rating of Nigerian listed banks. In contrast, ownership concentration significantly determines ESG rating, though the relationship is negative. Firm size was also found not to be a determinant of ESG rating in Nigerian listed banks. Practical implications—Institutions should be allowed to own large amounts of shares in Nigerian-listed banks, and bank regulators should implement policies to ensure that the banks remain viable in the future. Regulations should also be enacted to limit the amount of shares held by an individual shareholder in Nigerian-listed banks. Originality/value—The study investigates the effect of the following attributes, institutional ownership, ownership concentration, firm age, and firm size, on corporate ESG rating, as viewed from the Nigerian banking perspective. It aims to reveal whether these attributes determine ESG ratings in Nigerian NGX-listed banks.